The Role of Financial Technology In Promoting Modern Management Accounting In Commercial Banks: An Analytical Study of The Opinions of A Sample of Administrative Leaders In Private Banks In The Middle Euphrates Region - Galawi, Zainulabdeen; Abdulhussein, Muslim; Mohammed, Ali (Journal of Economics, Assets, and Evaluation, 2025)
The current research aims to uncover the role of financial technology through its dimensions (security, digital payment systems, social impact, innovation, perceived usefulness) in enhancing modern managerial accounting for commercial banks through its dimensions (activity-based costing, total quality management, balanced scorecard) among managerial leaders in private banks in the Middle Euphrates region. This objective arises from addressing the posed problem, which was summarised in the question: Is there a role for financial technology in enhancing modern managerial accounting in the commercial banks under study?.  To address this issue, the current research focused on a questionnaire tool, and accordingly, the research sample consisted of (112) administrative leaders. The research was based on a main hypothesis stating that there is no statistically significant relationship between financial technology and modern management accounting. The study problem was represented by the main question: to what extent does financial technology contribute to enhancing the applications of modern management accounting in private commercial banks in the Middle Euphrates region? The analytical descriptive method was used to achieve the research objectives and prepare its tools, using statistical programs (AMOS.V.29, SPSS.V.29). The research results indicated that financial technology represents a pivotal factor in developing modern management accounting systems, as it contributed to improving the accuracy of financial data and the speed of access to it, thereby supporting the administrative decision-making process.